2018
DOI: 10.1111/aos.13898
|View full text |Cite
|
Sign up to set email alerts
|

High rate of failed visual‐acuity measurements with the Amsterdam Picture Chart in screening at the age of 36 months

Abstract: Purpose In the Netherlands, youth health care physicians and nurses screen all children for general health disorders at Child Health Care Centers. As part of this, the eyes are screened seven times, with the first visual acuity (VA) measurement at 36 months with the Amsterdam Picture Chart (APK). The suitability of the APK has been questioned. Methods Children born between July 2011 and June 2012 born in the provinces Drenthe, Gelderland and Flevoland and invited for screening at 36 months were eligible. Paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
0
13
1
Order By: Relevance
“…The frequency of vision impairment in extremely preterm children has been reported as 2.0-3.1% (Leversen et al 2012;Holmstrom et al 2014, andFledelius et al 2015) compared to our finding of 3.0%. Holmstrom et al (Holmstrom et al 2014) found only 51% of extremely preterm children able to participate in optotype testing at 2.5 years and 32.1% failed optotype testing at 3 years in a recent Dutch study (Telleman et al 2019). In comparison with the cited studies, our subjects were less preterm on average in terms of gestational age and birthweight.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…The frequency of vision impairment in extremely preterm children has been reported as 2.0-3.1% (Leversen et al 2012;Holmstrom et al 2014, andFledelius et al 2015) compared to our finding of 3.0%. Holmstrom et al (Holmstrom et al 2014) found only 51% of extremely preterm children able to participate in optotype testing at 2.5 years and 32.1% failed optotype testing at 3 years in a recent Dutch study (Telleman et al 2019). In comparison with the cited studies, our subjects were less preterm on average in terms of gestational age and birthweight.…”
Section: Discussioncontrasting
confidence: 41%
“…) found only 51% of extremely preterm children able to participate in optotype testing at 2.5 years and 32.1% failed optotype testing at 3 years in a recent Dutch study (Telleman et al. ). In comparison with the cited studies, our subjects were less preterm on average in terms of gestational age and birthweight.…”
Section: Discussionmentioning
confidence: 96%
“…Conventional vision screening included measurement of visual acuity with the Amsterdam Picture Chart (APK) in 3y and with the Landolt-C chart at the ages of 3y9m and 5/6y. 7 , 8 Measurements are usually performed at a distance of 5 m. The line number per eye of smallest symbols that the child could read should be registered, but often testing was stopped as soon as a pass was obtained. Cut-off criteria for visual acuity are age-dependent.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of VA in children at the age of 36 months as part of population‐wide screening fails in 16.6% of children, in addition to 15.5% of children not reaching the threshold and, hence, cannot be done cost‐effectively (Telleman et al. ). The rates of failed measurement of VA are lower when performed by experienced orthoptists (Becker et al.…”
Section: Introductionmentioning
confidence: 99%